The Association between the rs35874116 Gene TAS1R2 Polymorphism with Caries Index - Pelangi Mumtazdhia; Ani Melani Maskoen; Bremmy Laksono; Witri Ardini (Faculty of Medicine, UIN (State Islamic University) Syarif Hidayatullah Jakarta, 2022)
Background: Dental caries is a multifactorial disease influenced by complex genetic and environmental factors. At least 27 gene polymorphisms have been identified that are associated with caries risk. Polymorphisms of genes encoding taste receptors, such as the TAS1R2 gene, can cause individual differences in perception and sensitivity to sweet tastes. Research shows that the TAS1R2 gene polymorphism is associated with the consumption of sweet foods, which affects increasing caries risk. This study aims to determine the relationship between the TAS1R2 gene rs35874116 polymorphism and the caries index in Tangerang Selatan population. Methods: This study is observational with a cross-sectional method involving 266 research subjects (45 males and 221 females; 20-55 years). DNA was extracted from venous blood using the Genomic DNA Mini Kit from Geneaid and the genotyping process using the rhAmp-SNP assay kit, which was analyzed using RT-PCR. Dental caries was assessed by calculating D(decayed), M(missing), and F(filled) on permanent teeth. The hypothesis between the TAS1R2 genotype and the DMF-T index was tested using the Mann-Whitney test, while the comparison between the TAS1R2 genotype and caries risk was tested using Kruskal-Wallis' test. The results of the study were considered significant if p<0.05. Results: The minor allele frequency was 16.5%. The proportion of TT, TC, and CC genotypes were 71.%, 24.1%, and 4.5%, respectively. According to WHO classification, the DMF-T index of all research subjects was 5.62, a high category. The group of subjects with the CC genotype had a higher DMF-T index (7.08; very high) than the group of subjects with the CT genotype (6.05; high) and TT (5.38; high). CT and TT genotypes with high risk were significantly lower than those with low-moderate caries risk. Conclusion: there is no significant association between the TAS1R2 gene polymorphism rs35874116 with the caries index value in the people in South Tangerang.